Green Banking Strategy to Support Business Sustainability in Banking Sector: A Literature Review - Kurniadi, Ade; Rahman, Andi Halim; Indriani, Farida (Research Horizon, 2024)
Public concern and awareness of climate change has made many business sectors start to think about implementing sustainability strategies in their business activities. Of course, this is related to accommodating the market for people who are already aware of environmental issues. In the banking world, this can mean using strategies to protect the environment, such as using digital technology to reduce paper use and reduce face-to-face meetings, which will indirectly have an impact on reducing carbon emissions in transportation modes. However, it turns out that excessive use of digital technology actually creates digital waste which has an equally negative impact on the environment. There is a need for a thorough understanding of the issue of digitalization which can be a double-edged sword for environmental sustainability. This research wants to see to what extent the banking sector in Indonesia has responded to this issue so that they can maintain their business while preserving the environment. This research uses a literature review method to search for broader information and filter it in order to see a bigger picture regarding banking sustainability strategies, Green Banking, throughout the world. Green banking implemented by banks can channel funds, especially on credit, to the community by implementing an eco-friendly environmental system.